Nonlinear 3D Photographic Material With Luminescent Visualization of Images - Martynovich, Evgueni F.; Frolova, Anastasia S.; Rakevich, Alexander L. (Laser & photonics reviews, 2025)
A new nonlinear volumetric photographic material based on a KCl crystal with activating doping with thallium salt has been created. This is a new medium of a new class of functional materials that has been forming in recent years and are intended for visualization, recording, digitization, storage, and study of 3D patterns of highly nonlinear interaction of femto‐ and attosecond laser pulses with optical media. In a KCl crystal, two new types of previously unknown, optically and thermally stable luminescence centers have been created for the first time. They form a latent image and allow its visualization. They are induced by laser radiation and have the following main characteristics: the maximum of the luminescence band is 640 nm, absorption is 423 nm, and the luminescence decay time constant is 35 ns for the first center. For the second center, these characteristics have the following values, respectively, 440, 365 nm, and 1.3 µs. The created material is also suitable for the production of volumetric optical media for direct laser recording of visual or digital information. A new nonlinear volumetric photographic material based on a KCl crystal with activating doping with thallium salt has been created. This is a new medium of a new class of functional materials that has been forming in recent years and are intended for visualization, recording, digitization, storage, and study of 3D patterns of highly nonlinear interaction of femto‐ and attosecond laser pulses with optical media. In a KCl crystal, two new types of previously unknown, optically and thermally stable luminescence centers have been created for the first time. They form a latent image and allow its visualization.